Long-term adverse outcomes associated with drug-eluting stents and bare-metal stent in patients with small coronary artery disease: a systematic review and meta-analysis - Chaudhary, Nabin; Bundhun, Pravesh Kumar; Shrestha, Sujan; Yan, He (Nepalese Heart Journal, 2018)
Objective: The main purpose of this meta-analysis was to compare the long-term adverse outcomes associated with drug-eluting stents (DES) and bare-metal stent (BMS) in patients with small coronary artery disease (CAD). Method: Randomized Controlled Trials (RCTs) and observational studies comparing the adverse outcomes such as mortality, major adverse cardiovascular events (MACE), myocardial infarction (MI), stent thrombosis (ST), target lesion revascularization (TLR), target vessel revascularization (TVR), and restenosis in small CAD patients receiving DES and BMS were searched from Embase, PubMed, and Cochrane Library databases. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated and the pooled analyses were performed with RevMan 5.3. Result: A total number of 4,106 patients with small CAD (2,123 patients received DES and 1,983 patients received BMS) have been included in this meta-analysis. Pool-analysis demonstrated that the risk of mortality, MACE, MI, ST, TLR, TVR, and restenosis were significantly lower in DES group, with OR 0.77(95%CI 0.59-0.99, P=0.04), 0.48(95%CI 0.41-0.56, P<0.00001), 0.74(95%CI 0.55-0.98, P=0.04), 0.51(95%CI: 0.26-0.98, P=0.04), 0.24(95%CI: 0.16-0.37, P<0.00001), 0.47(95%CI: 0.38-0.59, P<0.00001), and 0.24 (95%CI 0.14-0.43, P<0.00001), respectively. Conclusion: Compared with BMS, DES had lower rates of adverse clinical outcomes, and restenosis during long-term follow-up. Nepalese Heart Journal 2018; 15(1): 1-7